Plant‐ and Fish‐Derived n‐3 PUFAs Suppress Citrobacter Rodentium–Induced Colonic Inflammation. Issue 6 (12th February 2020) - Määttänen, Pekka; Lurz, Eberhard; Botts, Steven R.; Wu, Richard Y.; Robinson, Shaiya C.; Yeung, C. William; Colas, Romain; Li, Bo; Johnson‐Henry, Kathene C.; Surette, Marc E.; Dalli, Jesmond; Sherman, Philip M.
Abstract : Scope: Marine‐derived n ‐3 PUFAs may ameliorate inflammation associated with inflammatory bowel diseases. Plant‐derived n ‐3 PUFAs are thought to be inferior owing to shorter chain lengths. The aim of this study is to compare the impact of plant‐ and fish‐derived PUFAs on murine colitis. Methods and results: C57BL/6 mice are fed high fat (36% kcal) diets with either 2.5% w/w sunflower oil (SO), flaxseed oil (FSO), ahiflower oil (AO), or fish oil (FO). After 4 weeks, mice are orogastrically challenged with Citrobacter rodentium (10 8 CFU) or sham gavaged. Fecal shedding is assayed at 2, 7, 10, and 14 days post infection (PI), and fecal microbiota at 14 days PI. Colonic inflammation and lipid mediators are measured. Supplementation regulates intestinal inflammation with crypt lengths being 66, 73, and 62 ±17 µm shorter (compared to SO) for FSO, AO, and FO respectively, p  < 0.01. FSO blunts pathogen shedding at the peak of infection and FSO and AO both enhance fecal microbial diversity. FO attenuates levels of lipoxin and leukotriene B4 while plant oils increase pro‐resolving mediator concentrations including D, E, and T‐series resolvins. Conclusion: Plant and fish n ‐3 PUFAs attenuate colitis‐induced inflammation while exhibiting characteristic pro‐resolving lipid mediator metabolomes. Plant oils additionally promote microbial diversity. Abstract : Omega‐3 oils from flaxseed, ahiflower, and fish dampen infection‐induced colonic inflammation in mice as compared to sunflower oil–supplemented controls. The different oils elicit unique but partially overlapping lipid metabolomes at the site of infection during resolution. Plant oils primarily increase proresolving lipid mediators while fish oils dampen inflammatory eicosanoids. Plant oils additionally enhance microbial diversity.